2018
DOI: 10.1016/j.resuscitation.2018.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Post-arrest therapeutic hypothermia in pediatric patients with congenital heart disease

Abstract: Our data show that pediatric CHD patients who suffer cardiac arrest can be treated effectively and safely with TH, which may decrease the incidence of seizures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…After excluding the duplicated papers, review or meeting abstracts, and irrelevant articles, 60 articles were left for further screening by checking the full texts. 47 articles were excluded, of which, seven were overlapped studies [42][43][44][45][46][47][48], seven were performed in pediatric patients [49][50][51][52][53][54][55], two study contained patients with other disease besides CA and the data related to CA could not be obtained separately [16,56], three studies contained CA patients treated with other methods besides ECPR and the data related to ECPR could not be obtained separately [17,57,58], fifteen studies had no sufficient data [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and eleven studies only had therapeutic hypothermia arms (without controls) [37,[74][75][76][77][78][79][80][81][82][83]. Two...…”
Section: Resultsmentioning
confidence: 99%
“…After excluding the duplicated papers, review or meeting abstracts, and irrelevant articles, 60 articles were left for further screening by checking the full texts. 47 articles were excluded, of which, seven were overlapped studies [42][43][44][45][46][47][48], seven were performed in pediatric patients [49][50][51][52][53][54][55], two study contained patients with other disease besides CA and the data related to CA could not be obtained separately [16,56], three studies contained CA patients treated with other methods besides ECPR and the data related to ECPR could not be obtained separately [17,57,58], fifteen studies had no sufficient data [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73], and eleven studies only had therapeutic hypothermia arms (without controls) [37,[74][75][76][77][78][79][80][81][82][83]. Two...…”
Section: Resultsmentioning
confidence: 99%
“…Protective effects of hypothermia are most prominent in tissues vulnerable to ischemia, such as the brain or myocardium. Therapeutic hypothermia is used to treat patients experiencing out of hospital cardiac arrest, during pediatric resuscitation, and is commonly used during cardiac surgical procedures (as a means of cerebral protection) involving interruption of blood flow to the brain . Physiologic effects of hypothermia are manifold, including a significant reduction in the tissue's metabolic rate for oxygen and glucose .…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic hypothermia is used to treat patients experiencing out of hospital cardiac arrest, 14 during pediatric resuscitation, 15 and is commonly used during cardiac surgical procedures (as a means of cerebral protection) involving interruption of blood flow to the brain. 16 Physiologic effects of hypothermia are manifold, including a significant reduction in the tissue's metabolic rate for oxygen and glucose. 17,18 Although the effects of hypothermia have been well-established clinically, the mechanisms of its action remain elusive in many tissues, and specifically in skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…For the secondary outcome of overall survival, a pooled analysis of the 2 RCTs (very low certainty of effect, downgraded for inconsistency and imprecision) found no statistically significant benefit in either long-term or short-term survival of TTM 32 CÀ34 C compared with TTM 36 CÀ37.5 C. 141,142 One retrospective cohort study found no benefit in adjusted intermediate-term survival associated with TTM 32 CÀ34 C versus TTM 36 CÀ37.5 C. 149 Three cohort studies also reported no associated increase in adjusted short-term survival associated with the use of TTM 32 CÀ34 C compared with TTM 36 CÀ37.5 C. 124,143,149 Adverse outcomes: infection. A pooled analysis of the 2 RCTs found no statistical difference in culture-proven infection from TTM 32 C À34 C compared with TTM 36 CÀ37.5 C. 141,142 Four cohort studies reported infection; unadjusted outcomes were not pooled, but none of the studies showed a statistically significant difference in infection with use of TTM 32 CÀ34 C compared with TTM 36 C À37.5 C. 124,144,146,149 Adverse outcomes: recurrent cardiac arrest. Pooled analysis of the 2 RCTs found no difference in the rate of recurrent cardiac arrest from TTM 32 CÀ34 C compared with TTM 36 CÀ37.5 C. 141,142 Two cohort studies reported unadjusted recurrent cardiac arrest rates that could not be pooled; none of the individual studies showed statistically significant association of increased recurrent arrest with the use of TTM 32 CÀ34 C compared with TTM 36 CÀ37.5 C. 124,149 Adverse outcomes: serious bleeding.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Pooled analysis of the 2 RCTs found a significant increase in serious bleeding from TTM 32 C À34 C compared with TTM 36 CÀ37.5 C. 141,142 Two observational cohort studies reported unadjusted odds ratios for serious bleeding; none of the individual studies showed association of statistically significant increase in bleeding with the use of TTM 32 CÀ34 C compared with TTM 36 CÀ37.5 C. 124,149 Adverse outcomes: arrhythmias. Pooled analysis of the 2 RCTs found no statistical increase in arrhythmias from TTM 32 CÀ34 C compared with TTM 36 CÀ37.5 C. 141,142 Five observational studies reported unadjusted outcomes for arrhythmias; 1 reported an association of a statistically significant increase in arrhythmias; the other 3 studies reported no statistically significant increase or decrease in arrhythmias associated with the use of TTM 32 C À34 C compared with TTM 36 CÀ37.5 C. 124,144,146,147,149 Subgroup analysis: location of cardiac arrest. For the predetermined subgroup analysis by location of arrest (OHCA or IHCA), no meta-analyses could be completed because there is only 1 RCT for each subgroup and the observational studies had methodological heterogeneity.…”
Section: Consensus On Sciencementioning
confidence: 99%